Best Answer

The "answer" is the number that 'x' must be in order to make the statement true.

Here's a way to find out what the number is:

-42 = 7 + 7x

Subtract 7 from each side of the equation:

-49 = 7x

Divide each side by 7:

-7 = x

Q: What is the answer -42 equals 7 plus 7x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7x + 9 = 51 7x = 42 x = 42/7 = 6

7x+7=28x 28x-7x=7 21x=7 x=3

6 + 7x = -36 first, subtract 6 from both sides 7x = -42 then, divide both sides by 7 7x/7 = -42/7 x = -6 to check, put -6 back into the original equation: 6 + (7 x -6) = -36 6 - 42 = -36

42

- 7X + 10 = 52 subtract 10 from each side - 7X + 10 - 10 = 52 - 10 - 7X = 42 divide both sides integers by - 7 (- 7/- 7)X = 42/- 7 X = - 6 --------------------check in original equation - 7(- 6) + 10 = 52 42 + 10 = 52 52 = 52 ----------------checks

Related questions

7x + 9 = 51 7x = 42 x = 42/7 = 6

7x=42 x=42/7 or, x=6

7x+7=28x 28x-7x=7 21x=7 x=3

6 + 7x = -36 first, subtract 6 from both sides 7x = -42 then, divide both sides by 7 7x/7 = -42/7 x = -6 to check, put -6 back into the original equation: 6 + (7 x -6) = -36 6 - 42 = -36

42

- 7X + 10 = 52 subtract 10 from each side - 7X + 10 - 10 = 52 - 10 - 7X = 42 divide both sides integers by - 7 (- 7/- 7)X = 42/- 7 X = - 6 --------------------check in original equation - 7(- 6) + 10 = 52 42 + 10 = 52 52 = 52 ----------------checks

The answer to the math problem -3 7x plus 7 is x equals 1/3.

-7(x + 6) = -7x - 42

-x2 + x + 42= -x2 + 7x - 6x + 42= 7x - x2 + 42 - 6x= x(7 - x) + 6(7 - x)= (7 - x)(x + 6)

7x = 42 so x = 42/7 and therefore x = 6

31=7x-11, 31+11=7x, 42/7=x, x=6 :)

if the equation was 7x = 42. The answer would be x = 6